SLUM TOURISM VS PESONA INDONESIA (Comparative Study of Tourism Promotion Concepts in Indonesia and Effectiveness Theory) - Widagdo, Haidi Hajar; Feriyanti, Yang Gusti; Indriani, Indriani; Kurniawan, Ramdhan; Mahmudin, Tono (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Pesona Indonesia and Slum Tourism are two different branding concepts and have different tourist branding goals. Therefore, this research aims to analyze and compare the two tourism branding concepts and add effectiveness theory. This research is qualitative research with an exploratory approach. The data used in this research is secondary data that researchers obtained from books, scientific articles, credible websites, and a number of other sources that are commonly used in every research. These data were analyzed using the stages of data collection, data selection, data reduction, and drawing conclusions. The results of this research show that first The Indonesian tourism branding concept "Pesona Indonesia" aims to show the beautiful and charming face of Indonesia's nature. Meanwhile, on the contrary, the tourism branding concept using "Slum Tourism" offers the face of slum Indonesian settlements transformed into beautiful, neat and charming tourist attractions. Seccond, From the results of the comparative study carried out, the concepts of "Pesona Indonesia" and "Slum Tourism" have a number of striking differences, especially in the form of tourism that is branded and the typical tourists who are the targets of the two concepts. Last, based on the study of effectiveness theory, the researcher concludes that in order for the tourism branding concept to be more effective, the Ministry of Tourism and Creative Economy should marry/acculturate/integrate the two concepts so that they can work side by side. Keywords : Pesona Indonesia, Slum Tourism, Effectivenss Theory, Comparative Study.